Combined experimental and density functional theory study on the Pd-mediated cycloisomerization of o-alkynylnitrobenzenes - synthesis of isatogens and their evaluation as modulators of ROS-mediated cell death - Ramana, Chepuri V.; Patel, Pitambar; Vanka, Kumar; Miao, Benchun; Degterev, Alexei (European Journal of Organic Chemistry, 2010)
Highly selective cycloisomerization of o-alkynylnitrobenzenes, leading to isatogens, has been achieved by employment of a Pd-II complex. This reaction is very general and functional-group-tolerant. The possible mechanism of this reaction was investigated with the help of DFT calculations. Three possible pathways - namely, the addition of the nitro group either in (i) 5-exo-dig or (ii) 6-endo-dig mode and (iii) halopalladation - and subsequent intramolecular events have been considered and studied in detail. These investigations revealed that pathway (i) is the favored route to isatogen formation. A preliminary screening of the available isatogens reveals the 2-alkylisatogens to be novel ROS scavengers capable of inhibiting cellular necroptosis.
Keywords: Anthranil; cyclization; Density functional calculations; isatogens; Nitro-alkyne cycloisomerization; Palladium